Creating inclusive classrooms by engaging STEM faculty in culturally responsive teaching workshops - Erin Sanders O'Leary; Casey Shapiro; Shannon Toma; Hannah Whang Sayson; Marc Levis-Fitzgerald; Tracy Johnson; Victoria L. Sork (SpringerOpen, 2020)
Abstract Background As higher education institutions strive to effectively support an increasingly diverse student body, they will be called upon to provide their faculty with tools to teach more inclusively, especially in science, technology, engineering, and mathematics (STEM) classrooms where recruitment and retention of students from underrepresented and disadvantaged groups present long-standing challenges. Pedagogical training approaches to creating inclusive classrooms involve interventions that raise awareness of student and instructor social identities and explore barriers to learning, such as implicit bias, microaggressions, stereotype threat, and fixed mindset. Such efforts should focus on embracing diversity as an asset leveraged to benefit all students in their learning. In this paper, we describe the impact of multiday, off-campus immersion workshops designed to impart faculty with these tools. Based on analysis of workshop participant data, we report the resulting changes in faculty knowledge of factors affecting classroom climate and student success in STEM, attitudes about students, and motivation to adopt new teaching practices aimed at fostering equitable and culturally responsive learning environments. Results Key findings indicate that attendees (1) increased their knowledge of social identities and the barriers to learning in STEM classrooms, particularly those faced by students from underrepresented groups in STEM or socioeconomically challenged backgrounds; (2) changed their attitudes about students' abilities as science majors, shifting away from a fixed-mindset perspective in which characteristics, such as intelligence, are perceived as innate and unalterable; and (3) modified their teaching approaches to promote inclusivity and cultural responsiveness. Conclusion Faculty members, who are linchpins in the evolution of college classrooms into settings that provide students with equitable opportunities to succeed academically in STEM, can benefit from participating in immersion workshops structured to support their awareness of issues affecting classroom culture related to race/ethnicity, LGBTQ status, religious affiliation, ability, socioeconomic status, and other social identities that contribute to disparities in STEM achievement and persistence.